Screening and pharmacodynamic evaluation of the anti‐respiratory syncytial virus activity of butene lactones in vitro and in vivo. Issue 1 (10th September 2019) - Wang, Zhenya; Tan, Yayun; Mou, Xiaodong; Wang, Congcong; Li, Yuanyuan; Xiao, Fan; Hu, Xiaoning; Liu, Hongmin; Xu, Haiwei
Abstract: A series of butene lactones were synthesized and these compounds were tested for anti‐respiratory syncytial virus (RSV) activity in vitro. Three compounds exhibited an antiviral effect, the highest of which was compound 6b3 with an effective concentration 50% of 6.35 μM. The effects of 6b3 were then evaluated in vivo and a significant reduction in the lung index caused by RSV was detected. Reduced inflammatory infiltration and necrosis of the lungs were revealed by histopathology and gross pathology. Activation of an early immune response by 6b3 was also observed by cytokine analysis via a real‐time polymerase chain reaction. These results indicated that 6b3 has an anti‐RSV effect both in vitro and in vivo, and is a possible candidate compound for the development of an anti‐RSV drug in the future. Highlight: We synthesized a series of butene lactones and tested their effects against RSV in vitro and in vivo. Compound 6b3 can reduce CPE caused by viral infection in vitro, inhibit viral replication and regulate the inflammation response caused by RSV infection in vivo.